Image reconstruction method for a two-layer tissue structure accounts for chest-wall effects in breast imaging - Xu, Chen (2008)
We develop a new tomographic imaging reconstruction algorithm for a two-layer tissue structure. Simulations and phantom experiments show more accurate reconstruction of target optical properties compared with those results obtained from a semi-infinite tissue model for layered structures. This improvement is mainly attributed to the more accurate estimation of background optical properties and more accurate estimation of weight matrix for imaging reconstruction by considering the light propagation effect in the second layer. Clinical results of breast lesions are also presented to demonstrate the utility of this new imaging algorithm.